Evaluation and Genome Analysis of Bacillus subtilis YB-04 as a Potential Biocontrol Agent Against Fusarium Wilt and Growth Promotion Agent of Cucumber - Xu, Wen; Yang, Qian; Yang, Fan; Xie, Xia; Goodwin, Paul H.; Deng, Xiaoxu; Tian, Baoming; Yang, Lirong (Frontiers in Microbiology, 2022)
Cucumber wilt caused by Fusarium oxysporum f.sp. cucumerinum (Foc) is a highly destructive disease that leads to yield reduction of cucumber. In this study, strain YB-04 was isolated from wheat straw and identified as Bacillus subtilis. It displayed strong antagonistic activity against F. oxysporum f.sp. cucumerinum in dual culture, and exhibited significant biocontrol of cucumber Fusarium wilt with pronounced growth-promotion of cucumber seedlings. B. subtilis YB-04 could secrete extracellular protease, amylase, cellulose and β-1, 3-glucanase and was able to produce siderophores and indole acetic acid. Inoculation with B. subtilis YB-04 or Foc increased cucumber defense-related enzymes activities for PPO, SOD, CAT, PAL and LOX. However, the greatest increase was with the combination of B. subtilis YB-04 and Foc. Sequencing the genome of B. subtilis YB-04 showed that it had genes for the biosynthesis of various secondary metabolites, Carbohydrate-Active enzymes and assimilation of nitrogen, phosphorous and potassium. B. subtilis YB-04 appears to be a promising biological control agent against Fusarium wilt of cucumber as well as promoting cucumber growth.